Studi Kelayakan Bisnis Pendirian Usaha Ayam Bakar Halto (Halalan Thoyyiban) - Abdul Mutolib; Lilis Karnita Soleha (Universitas 45 Surabaya, 2024)
This study aims to analyze the viability of the establishment of a Halto baking chicken business from various aspects, including market, technical, management, finance, and the environment, the initiative offers a main menu of baking Chicken with a distinctive flavor that is processed using traditional recipes and highquality ingredients. At the same time to find out the validity study of business enterprise, this research belongs to the category of field research. (field investigation) The author uses a descriptive research approach, the main objective of this study is to determine whether the proposed business venture is said to be worth or to lose. The results of the research showed that the market demand for baked chicken in the target region is quite high, with consumer preference for authentic flavours and affordable prices. From a technical point of view, strategic location and adequate resources support efficient operations.